A single-phase nine-level inverter for renewable energy systems employing model predictive control - Kakosimos, Panagiotis; Pavlou, Konstantinos; Kladas, Antonios; Manias, Stefanos (Energy conversion and management, 2015)
•A nine-level inverter for renewable energy applications is investigated.•We have developed a model predictive controller enabling fast dynamic response.•Separate DC-link voltage regulation and neutral point potential balance are attained.•Asymmetric conditions in terms of solar radiation and voltage variation are tested.•System performance is validated by an experimental setup of 2 individual PV strings. In this paper a single-phase cascaded Multilevel Inverter (MI) consisting of full NPC bridges for renewable energy systems is investigated. The development of the introduced control strategy is based on the application of Model Predictive Control (MPC) technique meeting the required specifications of the individual voltage level regulation of each separate DC source and neutral point potential balance under unity power factor. Illustrating the effectiveness of the developed controller, two separate PV strings are controlled while being subject to transient phenomena related to asymmetric string conditions in terms of solar radiation and reference voltage variation. The inverter topology of full NPC bridges in cascade allows low current THD factor to be achieved using a simple inductor instead of complicated LCL filters benefiting also from low capacitor banks in the DC-link bus. The proposed MPC performance has been validated by experiments carried out on a cascaded MI topology delivering power from two separate PV system strings.